Language-responsive mathematics teaching and AEN learners in a CLIL context - Ní Ríordáin, Máire; Neville, Craig; Daly, Megan (Frontiers in Education, 2024)
IntroductionThis study explores the experiences of students with additional educational needs (AEN) in Irish-medium education (IME) mathematics classrooms within a Content and Language Integrated Learning (CLIL) context. The research investigates how language-responsive mathematics teaching and adapted summative assessments impact AEN students’ learning outcomes, addressing a critical gap in understanding the interplay between language proficiency and mathematical competencies in bilingual settings.MethodsA case study design was employed in a single IME primary school, focusing on five AEN students aged 9–10 years. Over a five-week intervention, participants engaged in small-group, language-responsive mathematics lessons tailored to their needs. Two summative assessments—one standard school-approved and one researcher-designed with language adaptations—were administered post-intervention. Data sources included teacher observations, reflective journals, and assessment results, analyzed through thematic coding and descriptive statistics.ResultsThe findings revealed that while language adaptations in assessments had minimal impact on overall performance, language-responsive lessons supported student engagement and understanding. Participants demonstrated improved confidence and participation, though challenges persisted in transitioning from concrete to abstract concepts and in language-intensive topics such as probability. The summative assessments were limited in capturing students’ full mathematical abilities due to cognitive and linguistic demands.DiscussionThe study highlights the potential of language-responsive teaching to enhance learning outcomes for AEN students in CLIL contexts. While adapted assessments showed limited efficacy, the pedagogical approach effectively addressed cognitive and linguistic challenges. Future research should explore scalable strategies for integrating language and content learning to support diverse learners in bilingual settings.